“You will have changed profoundly”: a letter writing exercise for 4th Year medical students - Beckman, Emily; Head, Katharine; Gramelspacher, Anna Maria (Research and Humanities in Medical Education, 2022)
Introduction: Reflective writing, an exercise where students respond to a prompt in writing and then read their writing aloud in class, is a core component of Narrative Medicine. Student writings often reveal truths about their own experiences moving through medical education, including the identity transformation they experience. Method: The purpose of this study was to ask fourth-year medical students (N=15) enrolled in Narrative Medicine elective courses at two large U.S. Midwestern medical schools to reflect on their medical school experience. The students were asked to write a letter in response to the following prompt: “if you could tell your 1st day of medical school self anything, what would it be?” Results: Through thematic analysis, the authors identified three major themes in these letters, including student reflections of medical school as a journey, identity transformation and identity management within medical school, and the value of important relationships and the role they play in the medical student experience. Discussion: We conclude the paper with a discussion on what we can learn from these student letters, calling for more attention to the vulnerability of students as they progress through medical school and more research on the kinds of transformation students experience. Medical students can be vulnerable, and the system that has been created for them to develop into empathetic, skilled physicians often contributes to that vulnerability. Therefore, institutions should not only allow students to reflect and give voice to their experience, but also encourage a reimagining of certain aspects of medical education.